Degradation of hexadecane by Pseudomonas aeruginosa with the mediation of surfactants: Relation between hexadecane solubilization and bioavailability. (November 2016) - Zhong, Hua; Wang, Zhiquan; Liu, Zhifeng; Liu, Yang; Yu, Mingda; Zeng, Guangming
Abstract: Degradation of hexadecane by Pseudomonas aeruginosa ATCC 9027 mediated with octylphenol ethoxylate (Triton X-100) or sodium dodecylbenzene sulfonate (SDBS) was studied to examine the relation between surfactant pseudo-solubilization and bioavailability for hydrophobic organic compounds (HOCs). For either of the surfactants, degradation of hexadecane in pseudo-solubilized form was delayed compared to hexadecane as a separate phase, showing a reduced availability of pseudo-solubilized hexadecane. When hexadecane with a quantity significantly higher than the pseudo-solubility was used as the carbon source, Triton X-100 enhanced the degradation whereas SDBS still showed inhibitory effect. Degradability test shows that Triton X-100 as the sole carbon source could be partially degraded, whereas SDBS could not. These results indicate that a reduction in HOC bioavailability may occur for surfactant-mediated bioremediation process, likely due to the barrier effect of surfactants at water-HOC interface. Graphical abstract: Pseudo-solubilization by surfactants reduces hexadecane bioavailability due to the blocking effect of surfactant. Highlights: Pseudo-solubilization by surfactants reduces hexadecane bioavailability. Triton X-100 is degradable and enhances hexadecane degradation in complex system. Blocking effect of surfactants accounts for reduction in hexadecane bioavailability.